A rare clinicoradiological presentation on giant thymoma extending bilaterally in both hemi-thoraces: Case report with review of literature - Zuber, Nibras; Ahmad, Shahbaz; Zubair, Ishma; Salar , Wamiq; Ahmad, Zuber (Indian Journal of Case Reports, 2025)
We present the case of a giant thymoma in a 70-year-old lady presenting as an intrathoracic mass lesion extending bilaterally, filling most of the space in both hemi-thoraces. The rarity of the occurrence of giant thymoma and unusual clinicoradiological presentation makes it an interesting case report. It is indicated that the diagnosis of thymoma should be considered in any intra-thoracic anterior mediastinal mass lesion.